“go on cam but dnt be dirty”: linguistic levels of identity assumption in undercover online operations against child sex abusers - MacLeod, Nicci; Grant, Tim (Language and Law / Linguagem e Direito, 2017)
One way in which linguists have been able to offer their expertise to undercover online policing in England and Wales is assisting police officers in the assumption of alternative identities in order to apprehend offenders in the context of the online sexual abuse and grooming of children. With reference to the historical Instant Messaging (IM) logs of a teenage female victim in a closed case of online sexual abuse, and the IM logs of trainee undercover officers (UCOs) as they attempt to impersonate her during a training task, we report here on work that draws on analyses of online interactions to develop a linguistic model that can be used to improve performance in identity disguise. We compare trainees’ performance before and after input from linguists in order to show how analysis at a number of linguistic levels can contribute to the training and support of specialist investigators of online child sex abuse.